First report of cowpea mild mottle virus in chia (Salvia hispanica) - Celli, Marcos Giovani (2016)
Chia (Salvia hispanica), a herbaceous plant of Lamiaceae family, has gained popularity due to its high concentrations of health-beneficial Omega-3 fatty acids. Plants showing different virus-like symptoms were observed in the principal chia production areas in Argentina. Some plants exhibited yellowing, mottled and blistering leaves, and others shortened internodes and leaf and stem deformation. The aim of this study was to identify the viruses infecting this crop. Forty symptomatic chia plants were collected from nine production fields in northeastern Argentina. The samples were tested for Alfalfa mosaic virus (AMV), Cowpea mild mottle virus (CPMMV), Cucumber mosaic virus (CMV), Tobacco mosaic virus (TMV) and Tospovirus group (I, II and III) by DAS-ELISA, for the genera Potyvirus by PTA-ELISA and for Begomovirus by PCR. CPMMV was detected in three plants with different kind of symptoms. In these plants, feather-like inclusions formed by virions were observed with transmission electron microscopy. ORF2 to ORF6 (2462 nucleotides) from the CPMMV viral genome was amplified by RT-PCR. Nucleotide (nt) sequence of the coat-protein gene (CP – ORF5) of the chia virus isolate was obtained and compared with 31 CPMMV sequences reported in GenBank. Results showed between 75.5% and 99.0% of nt identity, which is above the International Committee on Taxonomy of Viruses criteria for Carlavirus species differentiation. The phylogenetic analysis with the CP gene nt sequences revealed that the CPMMV chia isolate grouped with other CPMMV isolates from other plant species from Brazil, Ghana, India, Puerto Rico, Taiwan and USA, but were separated from four others from India. This is the first report of the presence of CPMMV in chia in the world. Although the other viruses were not detected in this work, it is possible that the different symptoms observed could be produced by a mixture of viruses because CPMMV was found in chia plants with different symptoms.